Comparing Effects of Reward Anticipation on Working Memory in Younger and Older Adults - Thurm, Franka; Zink, Nicolas; Li, Shu-Chen (Frontiers in Psychology, 2018)
Goal-directed behavior requires sufficient resource allocation of cognitive control processes, such as the ability to prioritize relevant over less relevant information in working memory. Findings from neural recordings in animals and human multimodal imaging studies suggest that reward incentive mechanisms could facilitate the encoding and updating of context representations, which can have beneficial effects on working memory performance in young adults. In order to investigate whether these performance enhancing effects of reward on working memory processes are still preserved in old age, the current study aimed to investigate whether aging alters the effects of reward anticipation on the encoding and updating mechanisms in working memory processing. Therefore, a reward modulated verbal n-back task with age-adjusted memory load manipulation was developed to investigate reward modulation of working memory in younger (age 20–27) and older (age 65–78) adults. Our results suggest that the mechanism of reward anticipation in enhancing the encoding and updating of stimulus representations in working memory is still preserved in old age. EZ-diffusion modeling showed age distinct patterns of reward modulation of model parameters that correspond to different processes of memory-dependent decision making. Whereas processes of memory evidence accumulation and sensorimotor speed benefited from reward modulation, responses did not become more cautious with incentive motivation for older adults as it was observed in younger adults. Furthermore, individual differences in reward-related enhancement of decision speed correlated with cognitive processing fluctuation and memory storage capacity in younger adults, but no such relations were observed in older adults. These findings indicate that although beneficial effects of reward modulation on working memory can still be observed in old age, not all performance aspects are facilitated. Whereas reward facilitation of content representations in working memory seems to be relatively preserved, aging seems to affect the updating of reward contexts. Future research is needed to elucidate potential mechanisms for motivational regulation of the plasticity of working memory in old age.